2022
DOI: 10.1097/prs.0000000000008906
|View full text |Cite
|
Sign up to set email alerts
|

Are We Working Harder for Less Pay? A Survey of Medicare Reimbursement for Hand and Upper Extremity Surgery

Abstract: Background: Ongoing concern for declining Medicare payment to surgeons may incentivize surgeons to perform more cases to maintain productivity goals. The authors evaluated trends in physician payment, patient charges, and reimbursement ratios for the most common hand and upper extremity surgical procedures. Methods: The authors examined Medicare surgeon payment, patient charges, and surgical volume from 2012 to 2017 for 83 common surgical procedures, incorporating the year-to-year Consumer Price Index to adj… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 19 publications
0
8
0
Order By: Relevance
“… 7 A decrease in reimbursement despite increase in surgical volume is not unique to hip arthroscopy and has been observed with other orthopaedic procedures. 26 , 27 For arthroscopic partial meniscectomy, LaPrade et al. 28 found that from 2005 to 2014, increasing hospital reimbursement outpaced declining surgeon reimbursement by 365%.…”
Section: Discussionmentioning
confidence: 99%
“… 7 A decrease in reimbursement despite increase in surgical volume is not unique to hip arthroscopy and has been observed with other orthopaedic procedures. 26 , 27 For arthroscopic partial meniscectomy, LaPrade et al. 28 found that from 2005 to 2014, increasing hospital reimbursement outpaced declining surgeon reimbursement by 365%.…”
Section: Discussionmentioning
confidence: 99%
“…21,22 Importantly, rising reimbursement for CTR may not reflect a direct increase in payment to surgeons over the years. 22 Finally, this study identified several procedures commonly performed concomitantly with CTR-the most common being cubital tunnel release, trigger finger release, and intercarpal or CMC arthroplasty. Past studies have demonstrated that additional procedures are commonly performed on the same day as CTR when multiple pathologies are present.…”
Section: Reimbursement Analysesmentioning
confidence: 99%
“…Based on the results of this study, a surgical procedure for proximal humeral fractures in adolescence seems “too much.” However, the incentive to operate in many health-care environments may create a substantial surgeon preference toward treating fractures operatively. There have been a decrease in some reimbursement schedules for orthopaedic procedures 2 and a concern for surgeons being incentivized to perform more cases to maintain productivity goals 3 ; decreased reimbursement is a known stressor contributing to surgeon burnout.…”
Section: Commentarymentioning
confidence: 99%